Ex Vivo and Simulation Comparison of Leakage in End-to-End Versus End-to-Side Anastomosed Porcine Large Intestine - Youssef Fahmy; Mohamed Trabia; Brian Ward; Lucas Gallup; Whitney Elks (Bioengineering, 2025)
Anastomotic leaks after colorectal resection are serious surgical complications. We have compared the integrity of two common colorectal anastomosis techniques, end-to-side (ES) and end-to-end (EE), to control specimens using a novel experimental setup that mimics anastomotic air leak tests, which are typically performed during surgeries. Freshly harvested porcine colonic sections from 23 F1 cross-species pigs were used. Pressure measurements and video imaging were used to monitor the ex vivo experiments on EE, ES, and Control specimens. Using EE (n = 16), ES (n = 12), and Control (n = 22) specimens, leak pressure was 282.6 ± 3.0 mm Hg for EE, 282.8 ± 2.6 mm Hg for ES, and 294.4 ± 12.1 for the Control. Time to leakage was 106.3 ± 28.1 s for EE, 263.9 ± 2127.0 s for ES, and 194.5 ± 90.2 s for the Control. We found that, while EE and ES have nearly identical leak pressures, ES was superior in terms of time to leakage and tissue expansion, which may explain why ES anastomoses have a lower clinical anastomotic leak rate. Two dependent variables representing stress and strain of colonic tissues were introduced. These variables showed ES was comparable to the Control. The experiments were simulated successfully using the finite element method (FEM). This research provides a reproducible ex vivo system with a corresponding FEM system to study the differences between anastomosis techniques and may help design anastomoses with lower leak rates and improve patient outcomes in colorectal surgeries.